2008
DOI: 10.1063/1.2825596
|View full text |Cite
|
Sign up to set email alerts
|

A comparative assessment of the perturbative and renormalized coupled cluster theories with a noniterative treatment of triple excitations for thermochemical kinetics, including a study of basis set and core correlation effects

Abstract: Abstract. The CCSD, CCSD(T), and CR-CC(2,3) coupled cluster methods, combined with five triple-zeta basis sets, namely MG3S, aug-cc-pVTZ, aug-cc-pV(T+d)Z, aug-cc-pCVTZ, and aug-cc-pCV(T+d)Z, are tested against the DBH24 database of diverse reaction barrier heights. The calculations confirm that the inclusion of connected triple excitations is essential to achieving high accuracy for thermochemical kinetics. They show that various non-iterative ways of incorporating connected triple excitations in coupled clust… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
18
0

Year Published

2008
2008
2014
2014

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 60 publications
(28 reference statements)
1
18
0
Order By: Relevance
“…However, it has been found that these methods can not provide balanced descriptions for different regions of potential energy surfaces, due to the spin contamination of the UHF reference function [13,14]. Besides these two approaches, other effective approaches have also been proposed, which include: the reduced multireference CCSD [15][16][17][18][19][20][21][22][23][24], the spin-flip method [25][26][27][28][29][30][31][32], the orbital-optimized CC approach [33][34][35][36][37][38][39][40], the completely renormalize CC approaches [41][42][43][44][45][46][47][48][49], active-space CC approaches [50][51][52][53][54][55][56][57][58][59][60]<...>…”
Section: Introductionmentioning
confidence: 99%
“…However, it has been found that these methods can not provide balanced descriptions for different regions of potential energy surfaces, due to the spin contamination of the UHF reference function [13,14]. Besides these two approaches, other effective approaches have also been proposed, which include: the reduced multireference CCSD [15][16][17][18][19][20][21][22][23][24], the spin-flip method [25][26][27][28][29][30][31][32], the orbital-optimized CC approach [33][34][35][36][37][38][39][40], the completely renormalize CC approaches [41][42][43][44][45][46][47][48][49], active-space CC approaches [50][51][52][53][54][55][56][57][58][59][60]<...>…”
Section: Introductionmentioning
confidence: 99%
“…In addition, as a result of rapid advances in computational technology in the last decade, computational chemists can now carry out quantum chemical and transition state theory (TST) calculations at a higher level than previously possible. Also, in relation to reaction kinetics, there have been considerable efforts in recent research in ab initio [7–13] and density functional theory (DFT)[14–19] methods aiming to calculate reliable reaction barriers, and in TST to calculate accurate reaction rate coefficients. [20–22] These efforts have led to recent calculations of highly accurate reaction rate coefficients by employing ab initio and/or DFT reaction paths or energy surfaces, and TST of various degrees of sophistication.…”
Section: Introductionmentioning
confidence: 99%
“…The CR-CC(2,3) method is an improvement over the CCSD(T) approach to overcome its deficiencies in describing systems involving biradical character. 61 Geometry optimizations are carried out at the UB3LYP 51 /6-31G(d) 52 level of theory. All the electronic calculations have been performed using the GAMESS code.…”
Section: Applicationsmentioning
confidence: 99%